Test The Inhibition of Beringin Leaf Extract (Ficus benjamina L.) Against The Growth of Candida albicans in Vitro - Santi Rodiah; Mades Fifendy; Gustina Indriati (Jurnal Serambi Biologi, 2022)
This study aimed to determine the inhibitory ability of F. benjamina leaf extract on the growth of the fungus C. albicans and the optimum concentration in inhibiting the growth of the fungus C. albicans. This research was conducted from October to December 2021 at the Microbiology Laboratory and Research Laboratory of the Department of Biology, Faculty of Mathematics and Science, Padang State University. This study is an experimental study consisting of 7 treatments and 3 repetitions with F. benjamina leaf extract at concentrations of 30%, 40%, 50%, 60%, 70% as well as negative control (sterile distilled water) and positive control (10% ketoconazole). Data for the diameter of the inhibition zone was analyzed by means of variance (ANOVA) and continued with further tests Duncan's Multiple Range Test (DMRT) further test. The results showed that the leaf extract of F. benjamina was able to inhibit the growth of the fungus C. albicans. The optimum concentration of F. benjamina leaf extract in inhibiting the growth of the fungus C. albicans at a concentration of 60% was 18.91 mm.